High coloration efficiency, high reversibility and fast switching response of nebulized spray deposited anatase TiO2 thin films for electrochromic applications. (20th November 2017) - Dhandayuthapani, T.; Sivakumar, R.; Ilangovan, R.; Gopalakrishnan, C.; Sanjeeviraja, C.; Sivanantharaja, A.
Graphical abstract: Highlights: Anatase TiO2 films were prepared by nebulized spray deposition technique. The deposited films showed a fast switching response in electrochromic study. TiO2 films exhibit a high reversibility of 99% and stability up to 1000 cycles. The highest coloration efficiency of 260 mC/cm 2 was obtained for the film. Abstract: Nebulized spray deposited electrochromic oxide thin films have shown better performance in electrochromic application due to the formation of finer particles on the substrate surface and improved contact between the substrate surface and film. In the present work, anatase phase TiO2 thin films with excellent electrochromic performance were prepared using nebulized spray deposition technique. The influence of substrate temperature on the electrochromic performance of TiO2 thin films was studied. In addition, various physical properties of the films were studied. The film prepared at lower substrate temperature of 200 °C exhibit a high coloration efficiency of 260.7 mC cm −2 at 600 nm, fast switching kinetics (bleaching time = 1.7 s, coloration time = 2.37 s), high reversibility of 99% and consistent stability of about 1000 cycles. The present report suggests that the nebulized spray deposited TiO2 thin films can perform efficiently in electrochromic applications.